2020
DOI: 10.1002/cpdd.843
|View full text |Cite
|
Sign up to set email alerts
|

The Bioequivalence of Two Peficitinib Formulations, and the Effect of Food on the Pharmacokinetics of Peficitinib: Two‐Way Crossover Studies of a Single Dose of 150 mg Peficitinib in Healthy Volunteers

Abstract: The marketed tablet formulation of peficitinib differs from the tablet used during the clinical trials. The bioequivalence of the marketed formulation and developmental tablet, and the food effect on the marketed formulation, were analyzed in 2 Japanese open‐label, randomized, 2‐way crossover studies in healthy male volunteers. Volunteers received a single oral dose of the marketed 150‐mg peficitinib tablet under fasted conditions (bioequivalence), and under fed or fasted conditions (food effect). Bioequivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…As absorption phase data was limited for patients with RA, we used prior information from the prior healthy volunteer model to construct the RA patient model. Although food intake has previously been shown to increase AUC inf by 27% and 36%, 12,13 food intake (fasted, high‐fat fed, or normal fed) in the phase 1 studies was not included in the models because apparent differences among food conditions were relatively smaller than IIV. In phase 2 and 3 studies, all patients with RA took the study drug in the morning in a fed condition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As absorption phase data was limited for patients with RA, we used prior information from the prior healthy volunteer model to construct the RA patient model. Although food intake has previously been shown to increase AUC inf by 27% and 36%, 12,13 food intake (fasted, high‐fat fed, or normal fed) in the phase 1 studies was not included in the models because apparent differences among food conditions were relatively smaller than IIV. In phase 2 and 3 studies, all patients with RA took the study drug in the morning in a fed condition.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic (PK) characteristics of peficitinib in healthy volunteers were investigated in previous clinical pharmacology studies. These studies showed that peficitinib was absorbed rapidly, as demonstrated by time to maximum observed concentration (T max ) of 1.0–1.8 hours, and that food intake increased the area under the plasma concentration–time curve (AUC inf ) by 27–36% 12,13 . The mean terminal half‐life (t 1/2 ) of peficitinib ranged from 2.8 to 12.9 hours, 12 and dose‐proportional exposure was demonstrated within the dose ranges studied across single doses (3–300 mg) 12,14 .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations